Analysis of Factors Affecting Fraud Financial Statements with Fraud Triangle Analysis - Suriany, Suriany; Kuntadi, Cris (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze factors affecting fraud financial statements with fraud triangle analysis. This writing uses the literature review method. The results show that there is an effect of financial stability on fraud financial statements. There is an effect of nature of industry on fraud financial statements. There is an effect of ineffective monitoring on fraud financial statements. There is no effect of financial target on fraud financial statements. There is no effect of change in auditor on fraud financial statements. Fraud financial statements can be caused by other things that vary according to the conditions of the company under study so that further research is needed to obtain answers on other variables that have an effect on fraud financial statements. Other factors that can affect fraud financial statements include external pressure, personal financial need, and capability.